(untitled) (Terr@ Plural, 2020)
This paper presents a geological heritage survey of the ‘Environmental Protection Area (EPA) of the Devonian Escarpment’ within the boundaries of Ponta Grossa (Southern Brazil), a region of notable geodiversity where socio-environmental conflicts are aggravated. The EPA is a conservation unit that embraces part of the Campos Gerais do Paraná, a rich geodiversity area that holds the last remnants of natural grasslands of the region. Consisting of the primordial stage of a geoconservation strategy, the survey for the inventory becomes an important tool to affect geoheritage protection. Sixty geological interest sites are presented with their main features, use recommendations, and were classified in geological thematic categories. These actions can guide the next steps for geoconservation of this special area.